i need a a little help, i know this isnt very hard i just cant find the answer..
i need give proofs to find the equivalences.
-p -> (p -> q)= tautology
where the frst p is the negation.
thanks any help will help
-p -> (p -> q)= tautology
well do you have proof methods like truth tables or semantic tableau, if you draw a truth table then the final column should be all true, and if you use semantic tableau, negate the whole formula and then show the tableau closes,
or using the fact that A -> B is logically equivelent to ¬A V B you can apply this rule twice and it should become clear, does this help?